(untitled) (Global Business Management Review (GBMR), 2024)
The prevalence of fast food consumption among students is on the rise. Although there is a growing study investigating consumption of fast food among adolescents and adults in Malaysia, little attention has been paid to university students. This is perhaps the first study to examine factors influencing fast food consumption within a sample of students in Universiti Utara Malaysia (UUM). Primary data from a survey were used. An ordered logistic regression analysis was utilised to estimate the odds of consuming fast food. The explanatory variables consisted of demographic factors, peer influence, knowledge about fast food, lifestyle and mental health. Findings of the present study showed that most of the students in UUM consumed 1 to 2 times of fast food per week. Males tended to consume more fast food than females. Fast food consumption was lower among Chinese students than Malays, Indians and those of other ethnicities. Students who have excellent academic performance were less likely to consume fast food than those with poor academic performance. High personal income was associated with increased odds of consuming fast food. Students who were influenced by their peers were more likely to consume fast food compared to those who were not. Living a healthy lifestyle was associated with reduced odds of fast food consumption. These findings are important in the sense that they can assist UUM and government in developing more effective measures aimed at lowering students’ fast food intake. Intervention measures directed toward reducing fast food consumption among UUM students who are males, are Malays, have poor academic performance, have high income and adopt unhealthy lifestyles may yield promising outcomes.